Financing Applications at Productive Zakat Institutions - Mohammad Ghozali; Zulfi Dian As Salam (al-Afkar, Journal For Islamic Studies, 2025)
This study examines the practice of productive zakat distribution through zakat institutions, focusing on potential positive impacts, the views of scholars, criticisms of the practice, and potential errors or non-compliance with sharia principles. Productive zakat distribution is aimed at empowering mustahik economically by providing interest-free business capital through zakat institutions. This study examines the views of scholars from various periods, identifying similarities and differences in their approaches to zakat distribution. The analysis also includes criticisms of zakat institution financing practices, including limitations in fund management, transparency, accountability, and compliance with sharia principles. Potential errors or non-compliance with sharia are also highlighted, including risks in zakat fund management and potential issues that may arise in productive zakat distribution practices. This study highlights the importance of effective risk management and compliance with sharia principles in zakat fund management, and emphasizes the need for transparency and accountability in zakat distribution practices to ensure a positive impact on communities in need.